2016
DOI: 10.1016/j.cub.2016.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Performed Four Hours after Learning Improves Memory Retention and Increases Hippocampal Pattern Similarity during Retrieval

Abstract: Persistent long-term memory depends on successful stabilization and integration of new memories after initial encoding [1, 2]. This consolidation process is thought to require neuromodulatory factors such as dopamine, noradrenaline, and brain-derived neurotrophic factor [3-7]. Without the release of such factors around the time of encoding, memories will decay rapidly [3, 5, 6, 8]. Recent studies have shown that physical exercise acutely stimulates the release of several consolidation-promoting factors in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 33 publications
8
75
1
Order By: Relevance
“…BDNF exerts its eff ects on the cognitive (Alesi et al, 2014) sphere through the abilities described above, and it is thought to infl uence learning (Leckie et al, 2014). Interestingly, an increase in BDNF aft er exercise is positively correlated with cognitive performance; this was also confi rmed recently by Van Dongen, Kersten, Wagner, Morris & Fernández (2016), who demonstrated that physical activity performed four hours aft er learning improves memory effi ciency, showing how the hippocampus improves its effi cacy in memory retention.…”
Section: Introductionsupporting
confidence: 53%
“…BDNF exerts its eff ects on the cognitive (Alesi et al, 2014) sphere through the abilities described above, and it is thought to infl uence learning (Leckie et al, 2014). Interestingly, an increase in BDNF aft er exercise is positively correlated with cognitive performance; this was also confi rmed recently by Van Dongen, Kersten, Wagner, Morris & Fernández (2016), who demonstrated that physical activity performed four hours aft er learning improves memory effi ciency, showing how the hippocampus improves its effi cacy in memory retention.…”
Section: Introductionsupporting
confidence: 53%
“…For example, several of the aforementioned studies found greater retention levels using a novel visuomotor precision task, whereas the current study did not find any additional benefits of performing a single bout of exercise following a task where visual information was encoded and probed. On the contrary, van Dongen et al demonstrated that acute high‐intensity exercise could improve long‐term retention in a visual memory task, albeit only when performed 4 hours post‐encoding. Other studies have revealed positive effects of both moderate‐ and high‐intensity exercise in a word‐list task when the bout was scheduled prior to the information to be remembered .…”
Section: Discussionmentioning
confidence: 98%
“…While close timing seems to be key for improvements, a recent study suggests that certain aspects of memory may actually benefit from a time delay [96]. For example, long-term memory assessed using a declarative memory task was improved following a four-hour delay between learning and exercise, compared with no delay [96].…”
Section: The Adaptive Capacity Modelmentioning
confidence: 99%
“…For example, long-term memory assessed using a declarative memory task was improved following a four-hour delay between learning and exercise, compared with no delay [96]. While this result seems to contradict the predictions of the ACM regarding proximity of exercise and cognitive challenge, it is important to note that cognitively demanding foraging typically takes place over several hours.…”
Section: The Adaptive Capacity Modelmentioning
confidence: 99%